1 - Metissage in Nineteenth Century Senegal: Hybrid Identity and French Colonialism in a West African Town - Hilary Jones, (Afrika Zamani, 2022)
This article argues that Saint-Louis’ peculiarity matched neither the identity of African societies of the interior nor that of metropolitan France. Nor was it identical to notions of sychretism or creolisation. On the contrary, this city gave birth to a cosmopolitan society with different national, ethnic, linguistic, and religious identities comparatively influenced as they were by their relation- ships with States and societies of the Senegal Valley region, and the trans- Atlantic trade. The article offers a re-reading of accounts by European travel- lers and officials combined with study of archival records, publications such as the Moniteur du Senegal, private papers and portrait photographs. Based on extensive fieldwork, the article sheds light on an overlooked aspect of African history and engages modern Atlantic and French colonial history by suggesting that these locations were not solely formed by elite uropean actors but by local inhabitants of the colonies and remote outposts.